Reducing rural households' annual income fluctuations due to rainfall variation through diversification of wildlife use: portfolio theory in a case study of south eastern Zimbabwe - Poshiwa, X.; Groeneveld, R.A.; Heitkönig, I. M.A.; Prins, H.H.T.; van Ierland, E. C. (Tropical conservation science, 2013)
Annual rural incomes in Southern Africa show large rainfall-induced fluctuations. Variable rainfall has serious implications for agro-pastoral activities (crop cultivation and livestock keeping), whereas wildlife and tourism are less affected. The aim of this paper is to investigate the role of wildlife income in reducing rainfall-induced fluctuations in households' annual incomes. We analyse costs and benefits from agro-pastoral systems in southeastern Zimbabwe by means of a two-tier longitudinal survey and wildlife benefits through analysis of wildlife revenues. We use the portfolio theory framework to investigate whether wildlife conservation has the potential for farmers to reduce risk associated with agricultural production. Results show that even though wildlife income is small, it tends to be less volatile than income from the agro-pastoral system. Furthermore, the addition of wildlife as an asset to the rural farmers' portfolio of assets showed that wildlife can be used as a hedge asset to offset risk from agricultural production without compromising on return. The potential of diversification using wildlife is, however, limited since agriculture and wildlife assets are positively correlated. We conclude that revenues from wildlife have some potential to reduce annual household income fluctuations, but only to a limited extent. We argue that if wildlife is organised on a more commercial basis, a more substantial role can be played by wildlife income in reducing variations in rural households' incomes.